Perception of the nursing team about pain in infants (Research, Society and Development, 2020)
The present study aims to understand the nursing team's perception of pain in infants hospitalized in a pediatric unit. This is a qualitative, exploratory and descriptive study carried out with the nursing team of the Pediatrics Unit of a Public Hospital in the Extreme South of Brazil. Data collection was carried out between April and May 2017 through semi-structured interviews recorded in audio, analyzed through textual discursive analysis. From the data analysis, three categories emerged: pain assessment based on professional experience and interaction with family members; difficulties and facilities for pain assessment; use of instruments for pain assessment. The main difficulties reported by nursing professionals are inherent in the non-verbalization of the infant and the lack of protocols or standards that may facilitate the perception of pain. It is concluded that the perception of the nursing team about pain in infants mainly through scales makes care simplified and effective, as it helps in defining the best therapy to be adopted, which denotes the need for training for professionals working in the pediatric unit in order to guarantee humanization in hospitals and better quality of care provided.